2017
DOI: 10.3389/fmicb.2017.00252
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O1 with Reduced Susceptibility to Ciprofloxacin and Azithromycin Isolated from a Rural Coastal Area of Bangladesh

Abstract: Cholera outbreaks occur each year in the remote coastal areas of Bangladesh and epidemiological surveillance and routine monitoring of cholera in these areas is challenging. In this study, a total of 97 Vibrio cholerae O1 isolates from Mathbaria, Bangladesh, collected during 2010 and 2014 were analyzed for phenotypic and genotypic traits, including antimicrobial susceptibility. Of the 97 isolates, 95 possessed CTX-phage mediated genes, ctxA, ace, and zot, and two lacked the cholera toxin gene, ctxA. Also both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 60 publications
4
31
1
2
Order By: Relevance
“…was seen throughout the years; however, slight peaks were observed during rainy, winter, and summer seasons. Similar seasonal trends have been observed from coastal area, but frequency is much higher as compared to current study [27,[37][38][39][40][41]. This may be due to lack of stagnant water reservoirs in the region and direct drainage of rain water into major river systems.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…was seen throughout the years; however, slight peaks were observed during rainy, winter, and summer seasons. Similar seasonal trends have been observed from coastal area, but frequency is much higher as compared to current study [27,[37][38][39][40][41]. This may be due to lack of stagnant water reservoirs in the region and direct drainage of rain water into major river systems.…”
Section: Discussionsupporting
confidence: 84%
“…In comparison to our observation, higher Vibrio infection rates ranging from 10% to 15% are reported from different parts of India [34,35]. Furthermore, surveillance studies from Bangladesh reported up to 18% of Vibrio infections among diarrheal populations [3,37]. Overall, our study depicts low levels of Vibrio spp.…”
Section: Discussioncontrasting
confidence: 79%
“…which is mostly associated sea animals and marine environments are also reported to be susceptible to the antibiotic [69]. Reduced susceptible has been reported in two West Africa countries [70,71], India [72] and Bangladesh [73] showing the possibility of the organism to develop resistance. It was highlighted in the Leclercq et al, [74], when antibiogram with quinolones are read, resistance to the most active fluoroquinolone in vitro indicates resistance to all fluoroquinolones in both Gram-negative and Gram-positive organisms An exception to this rule in Gram-negative organisms is the potential production of the AAC(6’)-Ib-cr enzyme, which affects ciprofloxacin but not levofloxacin [74].…”
Section: Discussionmentioning
confidence: 99%
“…The MIC values of the isolates are shown in Table 2. Reduced susceptibility to azithromycin has been documented in Bangladesh strains isolated between 2010 and 2014 [26]. Although isolates from Mozambique were susceptible to azithromycin in 2012-2013, 13 % of the isolates showed resistance phenotype in 2015 [27].…”
Section: Creeping Mic Of Azithromycinmentioning
confidence: 99%